Influence of Surface Roughness and Paint Coating on Corrosion Rate - Akbar, Dekrit H.; Purnami, Purnami; Budio, Sugeng Prayitno (Mechanical Engineering Department, Engineering Faculty, Brawijaya University, 2020)
The technology of paint and its application develop fast, driven by the increasing cost of energy, raw material and labors. In this study, paint was used as a corrosion inhibitor on the surface of API 5L while saltwater is used as the corrosive media. The coating was varied for three different cases, i.e. primary coating only, primary and color coating as well as primary, color and glossy coating. Meanwhile, surface roughness was varied for 0.6, 0.7 and 0.8 Î¼m. It is concluded that surface roughness and coating influence the corrosion rate. Smoother the surface and more coating layers lower the corrosion rate. Based on the study on API 5L steel, the lowest corrosion rate was obtained at 0.6 Î¼m with 3 paint coatings (primary, color paint and clear/gloss)